The Influence of the Application of the Cooperative Learning Model Type Teams Games Tournament (TGT) on the Mathematical Communication Skills of Students - Amelia, Bela; Ediputra, Kasman; Zulhendri, Zulhendri (Journal of Mathematics Science and Computer Education, 2024)
This research was motivated by students' low mathematical communication skills and the fact that the learning models used by teachers were not yet varied. Therefore, researchers tried to apply the TGT type cooperative learning model. This research aims to determine whether or not the TGT type cooperative learning model influences students' communication skills in vocational schools. This research is quasi-experimental research using a nonequivalent control group design. The population in this study was all students in class. Data was obtained from the initial and final ability tests in the form of mathematical communication questions. Data analysis was carried out using the t-test. Based on the data analysis and discussion results, a conclusion was obtained, namely that the mathematical communication skills of students who took part in learning using the TGT type cooperative learning model were higher than those using conventional learning.